PIDOTIMOD IN TREATMENT OF CHILDREN WITH ACUTE RESPIRATORY INFECTION WITH CONCOMITANT RECURRENT OBSTRUCTIVE SYNDROME - E. E. Lokshina; O. V. Kravchenko; O. V. Zaytseva ("Paediatrician" Publishers LLC, 2011)
Respiratory infections are frequent in children; consequently evaluation of prophylactic effectiveness of immunomodulators is needed. Objective: to evaluate of clinical, immunological efficacy and safety of pidotimod in complex treatment of children with acute respiratory infections (ARI) and obstructive syndrome. Methods: patients 3-10 years old hospitalized with ARI and obstructive syndrome participated the study. Children from first group (n = 30) were treated with pidotimod 400 mg 2 times daily during 14 days, children from control group (n = 30) received standard treatment without immunomodulatory agent. Dynamics of clinical course of a disease, immunological indices of blood (IL 2, 4 and 8, interferon α  and γ, IgA, M, G and total IgЕ) and swabs from mucous tunica of nasopharynx (sIgA) was estimated. The cases of recurrent ARIs during 12 months after the beginning of a study were controlled. Results: treatment with pidotimod induced statistically significant decrease of cytokines levels (IL 2, IL 8, and interferon γ) and increase of sIgA. The rate of recurrent ARIs during 12 months after the beginning of a study was lower than in control group. Recurrent episodes of bronchial obstruction occurred rarely. Conclusion: pidotimod has high clinical and immunological effectiveness and safety in treatment of children with ARI and concomitant obstructive syndrome.